Perbandingan Metode RT-PCR dan Tes Rapid Antibodi untuk Deteksi COVID-19 - Anita Suswanti Agustina; Rizana Fajrunni'mah (Jurnal Kesehatan Manarang, 2020)
COVID-19 is caused by SARS-CoV-2, which can spread rapidly from human to human. There are several laboratory tests to detect COVID-19, including the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) method and a rapid test antibody test to detect antibody reactions to SARS-CoV-2. Both methods have advantages and disadvantages of each, while the literature study comparing the two methods is currently limited. The type of research used is library research. Research materials have been collected from various journals, books, and guidelines, in line with the research topic, to obtain 24 library sources. The results of the literature study indicate that the target genes that can be used to detect COVID-19 RT-PCR methods include the N, E, RdRp, and ORF1a/b genes. The sensitivity of rapid antibody tests is known to range from 68−89%, while the specificity of rapid antibody tests ranges from 91−100%. RT-PCR has the advantage of being able to detect low-concentration antigens, but RT-PCR has weaknesses such as requiring expensive equipment and inspection fees, specially trained laboratory personnel, long working time, and high risk of exposure. Rapid antibody testing has advantages, including ease of sampling, lower testing costs, reduced risk of exposure to officers, does not require special equipment and space, but has the potential for cross-reactivity with other coronaviruses. Both the RT-PCR method and the rapid antibody test have their advantages and disadvantages, but rapid antibody testing with RT-PCR can improve the diagnosis of COVID-19. The results of this literature study are expected to be continued as a basis for further research on RT-PCR examination and antibody rapid test for COVID-19 detection in Indonesia, accompanied by information on onset time and time-testing with a large sample of research.